Integration versus Segmentation in Asian Financial Market: The Prospect of Regionalism in Asia - Roida, Herlina Yoka (UI Scholars Hub, 2009)
This paper draws the prospect of regionalism among inancial market in Asia (Indonesia, Malaysia, Philippine, Singapore, China, Hong Kong, Japan and South Korea). The irst part examines the correlation among them that lead to regional integration. The second part shows the possibility of integration or segmentation between Asia countries and world. The next part, tries to draw whether last inancial crises 1997 gave different result to the integration process. The correlation between Asia regional return and world return is tested by F-test (degree of signiicant 5%). The inal part of this paper gives a picture as to how the prospect of integration or segmentation return of Asia and world can initiate a process of economic integration towards a trade block development.